“We don't want to stand out, yet some of us do": The experience and responses of gender counter-normative students at Stellenbosch University - Beukes, A.; Francis, D.A. (South African Journal of Higher Education, 2020)
In 2016, The trans* Collective student activist group brought to light the erasure of gender counter-normative students’ contributions to the success of the #RhodesMustFall movement in 2015. Equally important, the Trans University Forum released a report in 2017 that compiled the experiences of gender counter-normative individuals at seven South African higher education institutions. The report evinced that universities are sites that marginalise and alienate gender counter-normative staff, students and workers. Employing life history research, the present article explores the experiences and responses of three gender counter-normative Stellenbosch University students as they navigate the university environment. Drawing on queer theory, the article highlights their challenges while at the same time it emphasises their agency and strategies of resistance to tackling cis-heteronormativity. The article concludes by highlighting how gender counter-normative students acknowledge and incorporate their relationships with others, allies and their communities as a collective response and action – collective agency – to challenge the normative, and sometimes adverse, university space.